Altered Expressions of NF1 and NF1-Related microRNAs as Biomarkers in the Diagnosis of Undifferentiated Pleomorphic Sarcoma - Zhang, Peng; Huang, Lingling; Ma, Pengwei; Niu, Xiaoying (Frontiers in Genetics, 2022)
Objective: Undifferentiated pleomorphic sarcoma (UPS) is a highly malignant, aggressive and pleomorphic subtypes of soft tissue sarcomas in adults, however, UPS is difficult to be diagnosed due to the lack of specific morphological and immunophenotypic features. Here, we aimed to identify new biomarkers for the diagnosis of UPS. Methods: The mRNA and protein expression of Neurofibromin 1 (NF1) in 68 pairs of UPS and adjacent normal tissue were detected using qPT-PCR and immunohistochemistry, and the correlation between NF1 protein expression and clinicopathological characteristics was analyzed. Then differentially expressed microRNAs (DE miRNAs) were identified between UPS tumor tissue and matched adjacent normal tissue using Hisep sequencing, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) of DE miRNAs were analyzed. The DE miRNAs of regulating NF1 gene were identified also using Targetscan and miRanda databases and validated by qRT-PCR. Results: Compared with adjacent normal tissue, both mRNA and protein expression of NF1 in UPS tumor tissue was significantly decreased, and the positive rate of NF1 protein was associated with tumor size, tumor metastasis and recurrence. 125 known DE miRNAs were identified from the screened miRNAs based on ︱log2(Fold Change)︳≥5 and P-value <0.05 (A total of 82 upregulated and 43 downregulated DE miRNAsin UPS tissue). Target genes regulated by DE miRNAs were enriched in pathways of metabolisms, RNA degradation, PI3K-Akt and Rap1 pathway. 11 miRNAs which were predicted to regulate NF1 gene were screened. After verification, the relative expression of has-miR-199-3p and has-miR-34a-5p were increased and decreased in UPS tumor tissue compared with those in adjacent normal tissue, respectively. Conclusion: NF1 and NF1-related microRNAs including has-miR-199-3p and has-miR-34a-5p may be novel biomarkers in diagnosis of undifferentiated pleomorphic sarcoma.